Cytoprotective role of octacosanol in lipopolysaccharide-induced inflammation - Tang, Jingrong; Yang, Zhi-Hong; Li, Wenling; Liu, Huaitian; Lucero, Diego; Sviridov, Denis; White, Olivia; Kun, Julia; Mukouyama, Yoh-suke; Remaley, Alan T. (Frontiers in Immunology, 2026)
Inflammation and endothelial dysfunction are key steps in the pathogenesis of atherosclerosis. Octacosanol (C28H58O, OCT), a very-long-chain saturated aliphatic alcohol (VLCA) with 28 carbons, is the main component of policosanol, a nutraceutical mixture of VLCAs (C20-C34) extracted from plants. Polycosanol in animal models is known to reduce atherosclerosis, but its mechanism of action remains unclear. This study investigates the pathways by which OCT alleviates LPS-induced inflammation in primary human aortic endothelial cells (HAECs). After overnight pretreatment with purified OCT, inflammation in HAECs was induced by lipopolysaccharide (LPS) at 100 ng/ml. The effects of OCT on the levels of pro-inflammatory cytokines, and molecules involved in inflammation signaling pathway, cell adhesion, and cell integrity were examined using quantitative RT-PCR, enzyme-linked immunosorbent assay, flow cytometry, or confocal microscopy in LPS-stimulated HAECs. The group of untreated HAECs was used as a control. OCT pretreatment of HAECs significantly reduced LPS-induced inflammatory responses, decreasing levels of IL-6, IL-8, and MCP-1 mRNA and protein, as well as TLR4, MYD88, TIRAP, TRAF6, and IRAK1 mRNA (p < 0.05). In a monocyte adhesion assay, LPS exposure increased human monocytic cells (THP-1) adherence to HAECs, whereas OCT pretreatment suppressed the LPS-induced adhesion of THP-1 to HAECs in a time- and dose-dependent manner, by blocking the mRNA and protein expression of adhesion molecules (VCAM-1, ICAM-1, P- and E-SELECTIN) (p < 0.05). OCT also suppressed mRNA and protein levels of CORTACTIN, VINCULIN, and TALIN, and inhibited focal adhesion and lamellipodia formation, cell deformation, and migration in response to LPS (p < 0.05). In addition, an endothelial permeability assay revealed that OCT pretreatment also improved endothelial cell integrity after LPS stimulation by preserving both adherens junctions and tight junctions formed by VE-CADHERIN, β -CATENIN, and Zonula Occludens-1 (ZO-1) (p < 0.05). In summary, the multiple cytoprotective effects of OCT against LPS-induced inflammation in endothelial cells could contribute to the anti-atherogenic properties of policosanol.